Contingency analysis of embedded generation deployment in distribution network - Mohd Herwan, Sulaiman; Aliman, O.; Siti Rafidah, Abdul Rahim (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/